GIS APPLICATION FOR MONITORING THE MINE AREAS - Weningsulitri Weningsulitri; Retno Damayanti; Tri Widarti Masduki; Jeani Sulistyowati; Muhamad Lutfi; Bagaraja Sirait (Indonesian Mining Journal, 2022)
Technology development is growing fast, such as satellite imagery and GIS for various applications, one of them is mining technology. Several regulations for the mining sector regarding the mandatory use of satellite imagery have been stated in some regulations to be implemented in mining sectors. Some mine environmental studies showed that the remote sensing and the GIS analysis could detect the small changes in its environment area with effective cost as the coverage of the sensory images is quite broad. The purpose is to monitor land alteration by observing the changes at the taking place, in either the number of voids or their area, using the 2019 and 2020 SPOT 6/7 image data. The algorithm change detection analyzes the number and void changing, mainly to provide a visual description of the void image trend and other applications. The trend of void numbers and its area can be predictable and correlated with the coal mine activities yearly. The results of 2019 SPOT 6/7 image showed that the total area of coal mine pit increased from 2% of the total area of the IUP to 2.53% in 2020. But, its allegation of environmental changes due to the mining activities will be strengthened by a ground check survey that cannot be conducted now.